2021
DOI: 10.1039/d1ma00017a
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dihydropyrimidinone-based nanocomposites as multifunctional anti-cancer drug

Abstract: Dihydropyrimidinones, a Biginelli compound, have been found to be a tumor inhibitor in the last decade. The novel carbon quantum dot- dihydropyrimidinone (CQD-DHPM) nanocomposites have been prepared by a simple...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…However, it has been found that the DHPM derivatives have better antifungal efficacy than DHPM as similar ZOI achieved with lower concentration of DHPM derivatives. [15] The antifungal ZOI test results of DHPM derivatives along with a control drug, itraconazole, have been demonstrated in Discussion:…”
Section: Methicillin--resistant Staphylococcus Aureus (Mrsa) Escheric...mentioning
confidence: 98%
See 1 more Smart Citation
“…However, it has been found that the DHPM derivatives have better antifungal efficacy than DHPM as similar ZOI achieved with lower concentration of DHPM derivatives. [15] The antifungal ZOI test results of DHPM derivatives along with a control drug, itraconazole, have been demonstrated in Discussion:…”
Section: Methicillin--resistant Staphylococcus Aureus (Mrsa) Escheric...mentioning
confidence: 98%
“…To this end, we screened our DHPM derivatives to evaluate anti-cancer activities against A549 cell lines along with anti- Synthesis and optmization of DHPM through oe-pot Biginelli reaction have been discussed in our previous reports. [11,15] Here, we prepared several amine derivatives of DHPM by substituting ethyl oxo-with ethylamine, ethanolamine, diethanolamine and triethanolamine. The synthesized pure DHPM compound has been substituted with various amine groups such as ethylamine(D1), ethanolamine(D2), diethanolamine(D3) and triethanolamine(D4) used for the preparation of DHPM derivatives.…”
Section: Introductionmentioning
confidence: 99%